Bank Reputation, Bank Commitment, and the Effects of Competition in Credit Markets - Dinç, I. Serdar (Review of Financial Studies, 2000)
This article discusses the effects of credit market competition on a bank's incentive to keep its commitment to lend to a borrower when the borrower's credit quality deteriorates. It is shown that, unlike in the borrower's commitment problem to keep borrowing from the same bank in "good" times, the increased competition may strengthen a bank's incentive to keep its commitment. Banks offer loans with commitment to the highest quality borrowers but, when faced with competition from bond markets, they also give these loans to lower quality borrowers. An increase in the number of banks has a non-monotonic effect; new banks reinforce a bank's incentive only if there are a small number of banks. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.